Multipath Content Transmission Mechanism Based Determining Cache Node Locations in CCN - Girija, K; Deepa, V. Vijaya (International Journal of Computer Sciences and Engineering, 2018)
In the point of internet users they give preference to content information, when compare to content information now current scenario gives more important to location based information. WSN face many limitations of cache techniques in terms of short communication range, reliability, security, privacy, mobility, poor processing capabilities, small storage and limited bandwidth availability. The services or data are offered to a broad category of users via the internet by the virtualization of the resources in the clouds. The tasks of the applications are executed after scheduling to proper machines and assigning with appropriate resources. The cache nodes which helps to find the user through fast and easiest way, reduce the hop count as an existing integer linear programming (ILP) problem when path of cache nodes destination to the user. So therefore ILP not able to solve in time, thought another method of approach have been introduced that is novel multipath routing transmission mechanism based on the network coding (MRNC). Quantitatively analysis of Proposed system Optimality of the shortest-path routing in Content-Centric Networking (CCN) in terms of application-level performance metrics. By using network coding technology, users Interest packet is divided into multiple child interest packet, and the content is divide and random linear codes and the content, thus the content is cache fragmentation. Content retrieval process is become into more child content. Proposed method more efficient to track paths, fastest short paths and reduce computation time comparatively integer linear programming (ILP).